Iranian Version of Overactive Bladder Symptom Scale: A Methodological Study - (:unkn) unknown (ARAS PART MEDICAL INT PRESS, 2018)
Objectives: This study was conducted aiming at evaluating the translation as well as psychometric properties of Persian version of overactive bladder syndrome score (OABSS). Materials and Methods: To this end, 100 menopausal women aged 45 years or older, who had at least one urgency episode lasting at least 3 months, were recruited in the study and asked to complete the OABSS and international consultation on incontinence questionnaire overactive bladder (ICIQ-OAB) questionnaire. The validity of OABSS was assessed using concurrent validity. In addition, the reliability of the questionnaire was calculated using test-retest reliability as well as Cronbach a. Results: Generally, the results of the study showed that there were significant correlations between the total score as well as single scores of the Persian version of OABSS and ICIQOAB sum score. Cronbach a, based on current samples, was 0.79 for the whole questionnaire. Moreover, the level of reliability calculated between the OABSS total scores at first and second time of administration enjoyed a good degree. Conclusions: Persian version of OABSS had an acceptable validity and reliability. According to the findings, the application of such questionnaires is beneficial in developing countries which are faced with resource scarcity.
Keywords: Overactive bladder; Validity; Reliability; Questionnaire; URINARY-TRACT SYMPTOMS; QUALITY-OF-LIFE; PATIENT PERCEPTION; CONDITION PPBC; SCORE; QUESTIONNAIRE; RELIABILITY; INCONTINENCE; URGENCY; PREVALENCE